2010
DOI: 10.1002/asia.200900561
|View full text |Cite
|
Sign up to set email alerts
|

General and Facile Syntheses of Metal Silicate Porous Hollow Nanostructures

Abstract: Porous hollow nanostructures have attracted intensive interest owing to their unique structure and promising applications in various fields. A facile hydrothermal synthesis has been developed to prepare porous hollow nanostructures of silicate materials through a sacrificial-templating process. The key factors, such as the concentration of the free metal cation and the alkalinity of the solution, are discussed. Porous hollow nanostructures of magnesium silicate, nickel silicate, and iron silicate have been suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 44 publications
0
57
0
Order By: Relevance
“…[28][29][30][31][32] Remarkably, these materials possessed the same mineral elements as those of previously reported magnesium silicate-based bioceramics and composite scaffolds. [28][29][30][31][32] Remarkably, these materials possessed the same mineral elements as those of previously reported magnesium silicate-based bioceramics and composite scaffolds.…”
Section: Introductionmentioning
confidence: 74%
“…[28][29][30][31][32] Remarkably, these materials possessed the same mineral elements as those of previously reported magnesium silicate-based bioceramics and composite scaffolds. [28][29][30][31][32] Remarkably, these materials possessed the same mineral elements as those of previously reported magnesium silicate-based bioceramics and composite scaffolds.…”
Section: Introductionmentioning
confidence: 74%
“…[1][2][3][4][5][6] Such properties mainly depend on the introduced metal species. Many metal ions embedded in mesoporous silica materials have been reported, [7][8][9][10][11][12][13][14][15] such as Fe 3+ , Ni 2+ , Zn 2+ , Cu 2+ , Mg 2+ and Nb 5+ .…”
Section: Introductionmentioning
confidence: 99%
“…(5)(6), while NH 3 is generated by the reaction shown in Eq. (7). The nanoparticles congregate around the gas and stick to each other; once the gas escapes, the hollow sphere remains.…”
Section: Vocsmentioning
confidence: 99%
“…Due to their excellent properties, high chemical and thermal stability, high specific surface area, high porosity, low density, and good biocompatibility [6], hollow nanomaterials show promise in environmental remediation applications. For example, hollow silicate nanostructures showed an excellent ability to remove Pb 2+ from contaminated water owing to their large specific surface area and unique structure [7]. Meanwhile, Liu et al [8] found that hollow CuO spheres showed excellent and rapid photocatalytic degradation of dyes, especially for methyl blue (MB).…”
Section: Introductionmentioning
confidence: 98%